Analysis of diversity and genetic grouping of wild Capsicum spp. populations with microsatellite markers - Gálvez-Muñoz, Yasmín Araceli; Palacios-Hernández, Keissy Maleni; Ruíz-Salazar, Régulo Ruíz; Álvarez-Rivera, José Abisenas; Castañón-Nájera, Guillermo (Ecosistemas y Recursos Agropecuarios, 2025)
This research was carried out emphasizing the analysis of the structural genetic diversity of 26 wilds populations of chili (Capsicum spp.), four microsatellite markers were used (SSRs). The SSR markers used, identifying 278 alleles, 92 of them were polymorphic. The highest number of alleles (97) was identified by the primer HpmsCa19, and the lowest number (53) was identified with Hpms-274. The Analysis of Molecular Variance (AMOVA) detected that 11.16% of the variability was due to regions, 27.12% between populations, and individuals within populations the remaining 70.51%. The statistic PhiRT=0.103 indicated that there are differences between regions, PhiPR=0.278 can be interpreted as an excess of heterozygous in the populations, while PhiPT=0.352, expressed that the individuals in each population showed a moderate effect of non-random mating. The conglomerate or cluster analysis united the evaluation between the populations into five groups. In the group of clusters, IV and V, the largest union occurred. Seven in conglomerate or group IV and nine in cluster or group V. Population of Ojo de Cangrejo Sierra (OCS) formed an individual group or cluster. The estimation of the structure of the evaluated populations was determined with a value of K=4 and ∆K=11.76. Based on the results obtained in the present study, it can be concluded that the simple sequence repeats (SSRs) markers were effective in identifying genetic diversity found and can be used as source of genes to be included in new varieties to help improve agricultural production and conserve important germoplasm.
Keywords: Molecular analysis; Capsicum spp; genetic diversity; population structure; simple sequences repeats